Galeri Kain Tenun Tradisional di Kabupaten Lombok Tengah - Gunada, Pramharta; Trimarianto, Ciptadi; Susanta, I Nyoman (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v9i02.66154, 2021)
Woven Fabric or generally called “Kain Tenun” is one of Lombok historical item that has high value of history and the beauty of its unique pattern. This condition brings a high potential of attracting tourists in order to lift up the local economy. Thus, it will be possible if a good facility is built, supported by a strategic location and to build a gallery is an excellent choice. As a public facility, a gallery would have to own a good circulation system, especially for the exhibition room which will be the most visited part of the place. Therefore, the design of the exhibition space will deeply affected from circulation in the room and how circulation pattern are created. There are several types of circulation system which can be chosen later based on each person needs and preference. An example of a room circulation system that is oftenly used is a linear circulation. The purpose of this research is to know and understand linear space circulation patterns and how is the right implementation towards exhibition room. This study was conducted with descriptive analysis and accompanied by visual images to help the analysis process. The outcome of this research shows that linear circulation is able to be implemented on an exhibition room of a gallery and it also have some advantages towards its security and comfort along the visitors and the showpiece. Keywords: gallery, exhibition, circulation